Fat-Free Mass Index, Visceral Fat Level, and Muscle Mass Percentage Better Explain Deviations From the Expected Value of Aortic Pressure and Structural and Functional Arterial Properties Than Body Fat Indexes - Gómez-García, Mariana; Torrado, Juan; Pereira, María; Bia, Daniel; Zócalo, Yanina (Frontiers in Nutrition, 2022)
Bioelectrical impedance analysis (BIA)-derived indexes (e.g., fat [FMI] and fat-free mass indexes [FFMI], visceral fat level [VFL]), are used to characterize obesity as a cardiovascular risk factor (CRF). The BIA-derived index that better predicts arterial variability is still discussed. Aims: To determine: (1) the association of classical (weight, height, body mass index [BMI], basal metabolic rate [BMR]) and BIA-derived indexes, with arterial properties deviations from expected values (arterial z-scores); (2) maximum arterial variations attributable to BIA-derived indexes; (3) whether the composition of total body, trunk and/or limbs is most closely associated with arterial variations. Methods: hemodynamic, structural, and functional parameters of different histological types of arteries were assessed (n=538, 7-85 years). Classical and BIA-derived indexes (fat mass and percentage, FMI, VFL, muscle mass percentage [PMM], FFMI and percentage) were measured (mono- and multi-segmental devices). Arterial z-scores were obtained using age-related equations derived from individuals not-exposed to CRFs (n=1688). Results: First, regardless of the classical index considered, the associations with the arterial properties showed a specific hierarchy order: diameters and local stiffness ˃ aortic and brachial blood pressure (BP) ˃ regional stiffness. Second, all the associations of FMI and FFMI with z-scores were positive. Third, FFMI exceeded the association obtained with BMI and BMR, considering structural z-scores. In contrast, FMI did not exceed the association with z-scores achieved by BMI and BMR. Fourth, regardless of CRFs and classical indexes, arterial z-scores would be mainly explained by: FFMI, VFL and PMM. Fifth, regardless of the body-segment considered, the levels of association between FMI and z-scores did not exceed those found for classic and FFMI. Total fat mass and trunk indexes showed a greater strength of association with z-scores than the FMI of limbs. Sixth, compared to lower limb FFMI indexes, total and upper limbs FFMI showed higher levels of association with z-scores. Conclusions: FFMI (but not FMI) exceeded the strength of association seen between BMI or BMR and structural z-scores. Regardless of the body segment analyzed, the associations between FMI and z-scores did not exceed those found with classic and FFMI. Arterial z-scores could be independently explained by FFMI, VFL and PMM.